Students’ Perception toward the Use of E-Learning in Intermediate Listening Course at English Department UNP - Tri Ayunda Nurmalita; Yati Aisya Rani (Journal of English Language Teaching, 2022)
This study aims to find out students’ Perception Toward the Use of E-learning In Intermediate Listening Course at the English Department UNP. The design of this research is the descriptive research design. The data was collected by using questionnaires and interview guidelines. In this study, the researcher used purposive sampling as a sampling technique to choose the participants. The participants of this study consist of 54 students from K1 and K2 2021 of English Education at UNP. The results of this study indicate that the students' Perception Of the Use of E-learning in the Intermediate Listening Course at the English Department UNP is positive. Based on the calculation of the average from all indicators, students’ perception toward using E-learning In the Intermediate Listening Courses is at 75% in the good category.